The efficacy and safety of different endovascular modalities for infrapopliteal arteries lesions: A network meta-analysis of randomized controlled trials - Guo, Julong; Ning, Yachan; Wang, Hui; Li, Yu; Su, Zhixiang; Zhang, Fan; Wu, Sensen; Guo, Lianrui; Gu, Yongquan (Frontiers in Cardiovascular Medicine, 2022)
Background: Endovascular treatment has become the first-line therapy for infrapopliteal artery occlusive disease (IPOD), while the optimal endovascular method remains to be determined. We performed a network meta-analysis (NWM) of randomized controlled trials (RCTs) to simultaneously compare the outcomes of different endovascular modalities for IPOD. Methods and Results: The Pubmed, Embase, and Cochrane databases were used as data sources. The NWM approach used random-effects models based on the frequentist framework. In total, 22 eligible RCTs (44 study arms; 1348 patients) involving nine endovascular modalities or combinations (balloon angioplasty (BA), drug-coated balloon (DCB), drug-eluting stent (DES), atherectomy device + BA (AD + BA), AD+DCB, balloon-expandable bare metal stent (BMS), self-expanding stent (SES), absorbable metal stents (AMS), and inorganics-coated stent (ICS) were included. BA had a lower 12-month primary patency rate than DCB (RR 0.50, CI 0.27, 0.93) and AD+DCB (RR 0.34, CI 0.12, 0.93). AD + DCB decreased 6-month TLR compared with AMS (RR 0.15, CI 0.03, 0.90), and DES decreased it compared with BMS (RR 0.25, CI 0.09, 0.71). DCB had a lower 6-month TLR rate than AMS (RR 0.26, CI 0.08, 0.86) and BA (RR 0.51, CI 0.30, 0.89). BA had a higher 12-month TLR rate than DCB (RR 1.76, CI 1.07, 2.90). According to the value of the surface under the cumulative ranking curve (SUCRA), AD + DCB was considered the best treatment in terms of primary patency at 6 months (SUCRA = 87.5) and 12 months (SURCA = 91). AD + BA was considered the best treatment in terms of 6-month TLR (SUCRA = 83.1), 12-month TLR (SURCA = 75.8), and 12-month all-cause mortality (SUCRA = 92.5). In terms of 12-month major amputation, DES was considered the best treatment (SUCRA = 78.6), while AD + DCB was considered the worst treatment (SUCRA = 28.8). Moreover, AD+BA always ranks higher than AD+DCB in the comparison including these two combinations. Subgroup analyses of modalities without stenting did not significantly change the primary outcomes. Conclusion: ADs showed noteworthy advantages in multiple terms for IPOD except for 12-month major amputation. AD+BA may be a better method for IPOD than AD+DCB.